Corrosion Process Detection of Tinplate in Deaerated Functional Beverage by EIS - 王吉会 付丛伟 高志明 夏大海 (Transactions of Tianjin University, 2013)
The corrosion process of tinplate in deaerated functional beverage was investigated by using electrochemi- cal impedance spectroscopy （EIS） combined with scanning electron microscopy （SEM） and energy dispersive spec- troscopy （EDS） techniques. The results reveal that the uncoated tinplate shows a poor corrosion resistance and the corrosion type is detinning. During the initial stage of immersion, EIS spectrum consisted of two capacitance arcs with obvious time-constant dispersion effect, which was attributed to the two-dimensional and three-dimensional inhomo- geneous distribution of the electrode surface. With the increase of immersion time, the capacitance arc of high fre- quency shrunk and degenerated, due to the corrosion of tin coating. The pore resistance of tin coating and the charger transfer resistance of substrate, which are determined from the electrochemical equivalent circuit, can be used as the indicators of tinplate corrosion process. The decrease of the pore resistance of tin coating indicates that the corrosion degree of tin layer becomes more severe, whereas the decrease of the charger transfer resistance of substrate implies that the corrosion degree of steel substrate also becomes more severe as the immersion time prolongs.